Science and Art: Research using artistic means - Wengrower, Hilda (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2012)
The paper encourages research in Arts Therapies, accepting mixed methodologies and emphasizing arts based research in order to achieve an evidence based practice. Some examples are brought.